Effect of WeChat and short message service on bowel preparation: an endoscopist-blinded, randomized controlled trial. Issue 2 (February 2019) - Wang, Shu-Ling; Wang, Qian; Yao, Jun; Zhao, Sheng-Bing; Wang, Li-Sheng; Li, Zhao-Shen; Bai, Yu
Abstract : Objective: Adequate bowel preparation is essential for a successful colonoscopy; clinical studies suggest reinforced education can improve the preparation process. However, there have been no trials to compare WeChat directions (the most widely used social media app in China) with those of the short message service (SMS). This study was aimed to assess the effect of WeChat and SMS on the bowel preparation quality. Participants and methods: This was a single-center, prospective, endoscopically blinded, randomized, controlled study. Patients in reinforced education groups received additional reminder messages by WeChat and SMS 2 days before colonoscopy. The primary outcome was bowel preparation quality evaluated by the Boston bowel preparation scale (BBPS) score and the rate of adequacy (BBPS score ≥6). Secondary outcomes included polyp detection rate, adenoma detection rate, and mean total adenomas detected. Patient tolerance level and subjective feelings were also evaluated. Results: The total BBPS score and the percentage of adequacy were significantly higher in the reinforced education groups compared with the control (WeChat vs. control, P <0.001; SMS vs. control, P <0.001). Moreover, statistically significant differences between the two interventions were found in the total BBPS score but not in the rate of adequacy ( P =0.007 and 0.561, respectively). The detection of adenomas, using multiplicity detection rate, advanced adenoma detection rate, and mean total adenomas detected, was much higher in the intervention groups ( P =0.039, 0.037, and 0.019, respectively). Conclusion: WeChat was superior to SMS for bowel preparation, although both of them may help improving the detection of adenomas. Abstract : Supplemental Digital Content is available in the text.